Die Vereinslizenzierung am Beispiel der Handball-Bundesliga - Carotenuto, R. (Beiträge zum Sportrecht, 63, 2023)
In this research work, the procedure of club licensing in German handball is for the first time subjected to a legal verification. The focus lies primarily on the examination and legal evaluation of the association regulations of the Handball-Bundesliga e.V. The structure of the study is based on the practical course of a handball season. The knowledge gained can be transferred to a far extent to professional women's handball and other team sports - in particular association football.